Skeletal metastasis detection with 99mTc-MDP bone scan and 18-F-FDG PET/CT scan in breast cancer patients - Manevska, Nevena; Besliev S.; Bozinovska N.; Makazlieva, Tanja; Stojanoski Sinisa; Miladinova, Daniela; Ugrinska, Ana (Springer Science and Business Media LLC, 2021)
Aim/Introduction: Breast cancer is the most commonly- diagnosed cancer worldwide in females. Skeleton is the most common site of metastasis spread (for breast cancer). Bone scan (BS) is a widely used, non-invasive nuclear medicine diagnostic tool for detecting bone metastasis (BM) in the early phase of the disease as well as after therapy. Although hybrid PET/CT imaging are more considered for staging and restaging the disease as well as evaluating treatment response, BS is still keeping its position as a highly sensitive method in detecting bone metastasis. The aim of our study was to compare the findings of bone scan and FDG-PET/ CT scan for detection of BM in breast cancer patients at initial staging of the disease. Materials and Methods: We retrospectively analyzed 25 patients with breast cancer who underwent both BS and PET/CT scan for detecting BM in the period 2019-2020. Whole body BS was performed 3 hours after iv injection of 740 MBq 99mTc-MDP. PET/CT was performed after 60 minutes of iv injection of 18F-FDG in accordance with standard protocols. Results: 25 patients were included in the study (age 53,56±11,55 years). BM affected both axial and appendicular skeleton in (n=7, 38,88%), axial skeleton only was affected in 8pts, while appendicular only in (n=4, 22,2%). Solitary metastases were detected in 5 pts, 3pts had 2 BM, 10pts had three or more BM. From all 25 patients, 7 pts (41,17%) had negative findings for BM with both methods, while 18 patients had positive findings with both methods. Among these positive findings, 10 patients (n=10/18; 55,55%) had identical metastatic bone foci detected with both methods. On the other hand, PET/CT scan revealed more foci of bone metastasis than BS in (n=7/18 patients; 38,88%), depicting BM in scapula, spine, sternum and iliac bones in different patients, that were not seen on bone scan. Bone scan presented more BM foci in only (n=2/18 patients; 11,1%). Patients with normal findings on BS did not reveal BM on PET/ CT scan which means there is a good correlation regarding false negative findings with both methods. Conclusion: BS and 18F-FDG-PET/CT are complementary modalities that are highly sensitive in evaluating BM in breast cancer patients. Hybrid imaging (SPECT/CT and PET/CT) because of the complementary value of CT may contribute to the diagnosis of BM. Bone scan is widely used, low cost, easy to perform diagnostic modality and remains the method of choice for detection of bone metastasis.